The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pcbi.1002787
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Circadian Cells Improve Resynchrony

Abstract: The mammalian suprachiasmatic nuclei (SCN) contain thousands of neurons capable of generating near 24-h rhythms. When isolated from their network, SCN neurons exhibit a range of oscillatory phenotypes: sustained or damping oscillations, or arrhythmic patterns. The implications of this variability are unknown. Experimentally, we found that cells within SCN explants recover from pharmacologically-induced desynchrony by re-establishing rhythmicity and synchrony in waves, independent of their intrinsic circadian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 54 publications
(90 reference statements)
4
48
0
Order By: Relevance
“…Moreover, Fig. 4B showed that GABA signaling allowed delayers to shift faster by increasing the width of the delay region, in agreement with previous research showing that shortened re-entrainment times could be explained by increases in the area of velocity response curves (Webb et al, 2012). Overall, GABA significantly increased the area of the delay region by 8.4% while decreasing the advance region area by 2.1%.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, Fig. 4B showed that GABA signaling allowed delayers to shift faster by increasing the width of the delay region, in agreement with previous research showing that shortened re-entrainment times could be explained by increases in the area of velocity response curves (Webb et al, 2012). Overall, GABA significantly increased the area of the delay region by 8.4% while decreasing the advance region area by 2.1%.…”
Section: Resultssupporting
confidence: 91%
“…It is clear that SCN cells are a heterogenous population with distinct oscillatory properties [61,[70][71][72]. Computational models have predicted that inclusion of more damped oscillators or placement of damped oscillators at more highly connected hubs in the network can yield higher and faster synchrony [73][74][75][76][77][78]. Notably, animals with as little as 25 per cent of SCN cells still show circadian rhythms in locomotor behaviour [79][80][81][82].…”
Section: Suprachiasmatic Nucleus and The Synchrony Of Cellular Circadmentioning
confidence: 99%
“…When the gene for Vip or its receptor, Vipr2 , were deleted, the sync index dropped to 0.05 (Aton, Colwell, Harmar, Waschek, & Herzog, 2005). Similarly, pharmacological disruption of cell-cell communication with drugs like tetrodotoxin or pertussis toxin can reduce the sync index of PER2::Luc rhythms in a SCN slice from nearly 0.7 to 0.1(Aton, Huettner, Straume, & Herzog, 2006; Webb, Taylor, Thoroughman, Doyle III, & Herzog, 2012). Importantly, the reduction in phase synchrony was accompanied by a broadened distribution of periods expressed by the cells, demonstrating that these genetic and pharmacological interventions disrupted the mechanisms underlying synchronization.…”
Section: Perturbations Reveal Synchronization Mechanismsmentioning
confidence: 99%